2010
DOI: 10.1051/0004-6361/201014331
|View full text |Cite
|
Sign up to set email alerts
|

The blazar content in theSwift-BAT hard X-ray sky

Abstract: Aims. We present the results from a study of the blazar content in the 15-150 keV map of the entire sky obtained analysing 39 months of data collected by the BAT telescope aboard the Swift satellite. Methods. We performed a cross-correlation of the significance map, obtained with a dedicated highly efficient algorithm for data processing and image reconstruction of the BAT survey data, with the blazar population of the Roma-BZCAT. After corrections for source confusion and spurious detections, we found signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The Roma‐BZCAT (Massaro et al 2011a) gives the X‐ray flux in the 0.1–2.4 keV band F X in units of 10 −12 erg cm −2 s −1 , while the radio flux density at 1.4 GHz S 1.4 is in mJy. Following Maselli et al (2010a), to express this ratio in a convenient non‐dimensional number, we multiplied the radio flux density by a bandwidth Δν, assumed equal to 1 GHz, and the value of the ratio was opportunely multiplied by a scale factor; for the Roma‐BZCAT data we have In this way, the value of the X‐ray to radio flux ratio equal to 10 −11 erg cm −2 s −1 Jy −1 corresponds to Φ XR = 1. We found that for well‐established L sources the values of Φ XR are smaller than 0.1, while for the H objects they are higher than 1.…”
Section: Bl L Ac Colours and Classificationmentioning
confidence: 99%
“…The Roma‐BZCAT (Massaro et al 2011a) gives the X‐ray flux in the 0.1–2.4 keV band F X in units of 10 −12 erg cm −2 s −1 , while the radio flux density at 1.4 GHz S 1.4 is in mJy. Following Maselli et al (2010a), to express this ratio in a convenient non‐dimensional number, we multiplied the radio flux density by a bandwidth Δν, assumed equal to 1 GHz, and the value of the ratio was opportunely multiplied by a scale factor; for the Roma‐BZCAT data we have In this way, the value of the X‐ray to radio flux ratio equal to 10 −11 erg cm −2 s −1 Jy −1 corresponds to Φ XR = 1. We found that for well‐established L sources the values of Φ XR are smaller than 0.1, while for the H objects they are higher than 1.…”
Section: Bl L Ac Colours and Classificationmentioning
confidence: 99%
“…We find 74 more sources, the largest fraction of which are blazars (16 BZB, 18 BZQ, and 9 BZU), followed by other AGNs (among which is the well known FR I radiogalaxy M87), the starburst galaxy NGC 253, and a few pulsars; 14 sources are unidentified. We note that, according to Maselli et al (2010), the number of spurious correspondences for such a low σ T value is ∼20%.…”
Section: Properties Of the Resulting Samples Of Sourcesmentioning
confidence: 82%
“…In the effort of increasing the list of objects emitting both in the BAT and in the LAT energy ranges we consider the adoption of a lower significance threshold. Taking into account the results obtained by Maselli et al (2010) in the cross-correlation of the BZCAT Blazar Catalogue (Massaro et al 2009) with the 39-month 15-150 keV BAT map (Cusumano et al 2010a) we adopt σ ⋆ T = 3. From their analysis, carried out at |b| > 10 • , Maselli et al (2010) found that the adoption of σ ⋆ T follows in a fraction of ∼ 3% of related spurious associations; this value is presumably underestimated at |b| < 10 • due to the higher density of sources.…”
Section: Correspondences Of 1fgl Sources With the 54-month Hard X-ray...mentioning
confidence: 99%
“…It was detected by the Fermi/LAT with a 5σ significance (Acero et al 2015). It is also a strong X-ray AGN observed by Swift with a flux of 3.22 ×10 at 0.1−2.4 keV (Maselli et al 2010). The optical image shows signs of post-merger with unusual distribution of dust .…”
Section: +315 (J2203+3145)mentioning
confidence: 98%